The molecular biology of DNA replication in the archaeon Sulfolobus solfataricus - Beattie, T; Thomas Beattie (2012)
DNA replication is essential for the propagation of all living organisms. The ability of a cell to accurately duplicate its entire genome is dependent upon the activity of numerous proteins. Identifying the molecular mechanisms by which these proteins act, and determining how they are physically and functionally coordinated at sites of active DNA replication, is central to understanding this essential cellular process. Archaea possess a DNA replication machinery which is ancestral to the one present in eukaryotes, and thus these organisms serve as simplified model systems for understanding the complexities of eukaryotic DNA replication. This thesis investigates the molecular mechanisms underlying Okazaki fragment maturation in the crenarchaeon Sulfolobus solfataricus, which is essential to the completion of lagging strand DNA replication. Reconstitution of Okazaki fragment maturation in vitro demonstrated that the activities of three enzymes – PolB1, Fen1, and Lig1 – are required for this process in S. solfataricus. Furthermore, it was shown that optimum coordination of their three distinct activities is dependent on the ability of PolB1, Fen1 and Lig1 to simultaneously interact with a single PCNA ring, providing evidence for a mechanism of multi-enzyme coordination which may be universally employed by DNA sliding clamp proteins. The importance of protein flexibility in the accommodation of multiple proteins around a single PCNA was also investigated. Finally, the physical coordination of one of these key maturation enzymes – PolB1 – with other replisome proteins was examined. It was demonstrated that PolB1 exists in a trimeric complex in vivo with two previously unidentified factors, raising the possibility of uncharacterised activities and interactions for this crucial enzyme. Taken together, these data provide new insights into functionally important protein-protein interactions within the archaeal replisome, and facilitate a greater understanding of the DNA replication machinery in both archaea and eukaryotes.